ULTRASONOGRAPHY IN ASYMPTOMATIC DENSE BREAST: A SYSTEMATIC REVIEW - Abdulloh, Arizal (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Breast cancer is a group of abnormal cells in the breast that continue to grow in multiples. Eventually these cells form a lump in the breast. If the cancerous lump is not controlled, the cancer cells can metastasize to other parts of the body. Metastases can occur in the axillary lymph nodes or above the scapula. In addition, cancer cells can nest in the bones, lungs, liver, skin and under the skin. Ca Mamae is a malignancy of the breast tissue which can originate from the ductal or lobule epithelium. Breast cancer ranks as the second leading cause of mortality in women who have been diagnosed with the disease. According to some studies, screening women for breast cancer once a year beginning at the age of 40 can reduce the risk of dying from the disease by approximately 40 percent. It is well acknowledged that mammography is an effective screening procedure for detecting breast cancer in its early stages; yet, the test is not without its limitations, particularly for women who have dense breasts. The sensitivity of mammography is reduced when performed on people who have dense breast tissue. In addition, women who have dense breast tissue have an increased risk of getting breast cancer, despite the fact that mammography has a lower detection rate for dense breast tissue. Mammographically undetected cancer can sometimes be found in women with dense tissue by the use of ultrasound screening, which can be performed manually or automatically. Studies have shown that ultrasonography makes a significant improvement in the diagnosis of clinically significant tumors that are relatively small, predominantly invasive, and lack lymph nodes. The use of supplemental breast ultrasonography in the population of women who have mammographically dense breast tissue makes it possible to detect tiny breast tumors that would have been occult otherwise. An elevated rate of biopsies is connected with the possibility of unfavorable consequences for the women who fall into this intermediate risk category.